Three-Dimensional Simulation of the McPherson Suspension System - Slavica Mačužić; Jovanka Lukić; Dragan Ružić (Tehnički Vjesnik, 2018)
Suspension system of a vehicle is one of the most important components of a vehicle that directly affects the safety, performance, noise level. Designing mechanisms of suspension system of the vehicle is a very complex task. At the beginning it is necessary to realize many requirements relating to the suspension system. McPherson suspension system is most commonly used on the front of the vehicle. Its application is most reflected in better movement of vehicles through the cornering as well as in a comfortable ride. Modern methods of construction of the system and its components involve the use of certain software packages. In this paper, using CATIA software package, numerical simulations were carried out for the most important parts of suspension. Finite element analysis was performed of the entire system to analyze effective stress and deformation changes in the function parameters in the analysis.